Simulating a Memory: Commemorative Dedications in Books between 1950–1989 - Valonis, Jonas (Vilnius University Open Series, 2025)
The article analyses commemorative dedications in books from 1950 to 1989. Dedications and inscriptions in books are examined as a way of communication of social subjects during the period of the highest growth of popularity of dedications in the 1960s and 1970s during the second Soviet occupation of Lithuania. The research revealed that the practice of dedicating a book was most popular in the individual and institutional media. Wooden language was introduced into dedications by authorities as a way of shaping behavior. It was taken by some individuals and used in individual dedications, which strengthened the ties between individuals and the authority rather than in-between individuals. Still, some individuals only simulated dedications or acted passively in referring to any entities/individuals in dedications, and the use of wooden language became widely established. Such authors managed to write their own authentic texts, In this way, they preserved authentical individual history rather than the one enforced by the regime.